Penerokaan Konsep Individualisme dan Kolektivisme dalam Mencapai Kegembiraan - Abdul Rashid Abdul Aziz; Muhammad Nubli Abdul Wahab; Sabihah Johan; Amin Al Haadi Shafie; Nur 'Ain Mustafar (Universiti Malaysia Pahang Al-Sultan Abdullah Publishing, 2025)
Indexed by MyCite